Observation of an improved healing process in superficial skin wounds after irradiation with a blue‐LED haemostatic device. Issue 6 (12th January 2016) - Cicchi, Riccardo; Rossi, Francesca; Alfieri, Domenico; Bacci, Stefano; Tatini, Francesca; De Siena, Gaetano; Paroli, Gaia; Pini, Roberto; Pavone, Francesco S.
Abstract : The healing process of superficial skin wounds treated with a blue‐LED haemostatic device is studied. Four mechanical abrasions are produced on the back of 10 Sprague Dawley rats: two are treated with the blue‐LED device, while the other two are left to naturally recover. Visual observations, non‐linear microscopic imaging, as well as histology and immunofluorescence analyses are performed 8 days after the treatment, demonstrating no adverse reactions neither thermal damages in both abraded areas and surrounding tissue. A faster healing process and a better‐recovered skin morphology are observed: the treated wounds show a reduced inflammatory response and a higher collagen content.Blue LED induced photothermal effect on superficial abrasions. Abstract : The Blue LED photocoagulator device enables an immediate stop of bleeding and an improved healing process in superficial skin wounds. These results were demonstrated in an in vivo study, in rats.